Estudos sobre a qualidade ambiental da microbacia do Córrego Lagoinha, para subsidiar a implantação de um parque linear, Uberlândia (MG) - Lima, Luis (2015)
This research has goal at understanding the evaluation of the environmental quality of water and sediment from the watershed Stream Pond. We also analyzed the environmental impacts of urban activities on the rise, directly focused on environmental health, based on the physical analysis, chemical and biological water and sediments. To achieve the proposed objectives, we used data collection, theoretical information regarding the topic, survey of the main points of anthropogenic degradation. The samples of water and sediments were collected in 1 high course and at the midpoint 2 course in stream Pond in the dry season and rainy. The results of physical and chemical analysis, water were framed as class II. Among the parameters analyzed are: air temperature and water; pH- hydrogen ionic potential; turbidity; CODChemical oxygen demand; BOD- biochemical oxygen demand; DO dissolved oxygen; fecal coliforms; TDS- total dissolved solids; OM- organic matter; electrical conductivity; nitrite and nitrate; chlorides and sulfates; total hardness; free residual chlorine; Hydrogen sulfide fluorides and cyanides and potentially toxic metals. We can conclude that water and sediment are non-standard physical, chemical and biological qualities allowed for parameters related to fecal coliforms, total, organic matter, phosphate, conductivity, ammonia nitrogen, iron, chromium, nickel, lead in water and copper and lead in the sediment. It was found in this research, it will take more commitment from the government in carrying out projects that enable the sustainability of the watershed Stream Pond.